Kualitas Pelayanan Administrasi di Desa Noelbaki Kecamatan Kupang Tengah Kabupaten Kupang - Herliana Auskase, Maria; Pradana, I Putu Yoga Bumi; Magdalena Lino, Maria (Policy, Law and Political Research Center, 2024)
One of the most crucial tasks of government is to ensure quality public services for citizens. Therefore, government agencies are often referred to as “public servants” or “public service”. In the provision of services to the community, there are still many service implementing employees who do not understand how important quality services to citizens are and have not been fully implemented properly. The purpose of this study was to understand how the quality of service administration in Noelbaki Village, Central Kupang Sub-district, Kupang Regency. This study used qualitative research methods, which are descriptive in nature. The findings of this study show that the quality of community services at the Noelbaki Village Office, seen from the perspective of the five dimensions that affect administrative services, there are two aspects that have not run optimally. Therefore, employees should further improve the quality of services and improve their service skills and discipline.